PENGARUH PENDEKATAN PEMBELAJARAN TAKTIS DAN TEKNISTERHADAP HASIL BELAJAR KETERAMPILAN SEPAKBOLA - Fernando, Ricky (2014)
Penelitianinihendakmengkajimengenaiefektivitaspendekatanpembelajarantaktisdanteknisterhadaphasilbelajarketerampilansepakbola.Hasilpenelitianinidiharapkandapatdijadikansebagaialternatifsolusidalamrangkapengembangankualitaspembelajaransepakbola.Metode yang digunakandalampenelitianiniadalahmetodeeksperimendengandesainpost only design. Populasidalampenelitianiniadalahsiswaputrakelas XI SMA Labschool UPI Kota Bandung sebanyak 60 siswa.Teknikpengambilansampelmenggunakanteknik Purposive Sampling.Waktupenelitianyaituselama 2 bulan, jumlahperlakuan 18 kali pertemuan, denganfrekuensi 1 minggu 3 kali. Instrumen yang dipilihpenulisadalahtesketerampilansepakboladanteskemampuanbermain (GPAI).untuksiswasekolahmenengahatastesketerampilansepakbolahanyamengambiltesakhirketerampilansepakbola.Penulismenggunakanempatbentuktesyaitutespassing and stoping, heading, dribbling dan shootingdanteskemampuanbermain (GPAI).Berdasarkanhasilanalisismakadapatdisimpulkan: (1) Terdapatpengaruh yang signifikanpendekatanpembelajarantaktisterhadaphasilbelajarketerampilansepakbola. (2) Terdapatpengaruh yang signifikanpendekatanpembelajaranteknisterhadaphasilbelajarketerampilansepakbola. (3) Terdapatperbedaanpengaruhpendekatanpembelajarantaktisdanteknisterhadaphasilbelajarketerampilansepakbola, namunpendekatantaktislebihmemberikanpengaruh yang signifikanterhadaphasilbelajarketerampilansepakboladibandingkanpendekatanpembelajaranteknis This study aim to study about effectiveness of tactical and technique learning approach toward learning outcome of soccer skill. The result of this study is hoped can made to become as alternative of solution in order to develop the quality of soccer learning.The method used in this study is experiment method with post only design. The population in this study are male students of class XI SMA Lab school UPI, Bandung as much as 60 students. The sampling technique used Purposive Sampling. The time of study lasted for 2 months, the number of treatment is 18 time of meetings, with frequency 3 time in one week. The instrument selected by author is soccer skill test and playing ability test (GPAI). For senior high school students, soccer skill test only take soccer skill posttest. The author used four form of test namely passing and stopping, heading, dribbling and shooting and playing ability test (GPAI). Based on analysis result, it can be concluded that: (1) There is significant influence of tactical learning approach toward learning outcome of soccer skill. (2) There is significant influence of technique learning approach toward learning outcome of soccer skill. (3) There is influence difference of tactical learning and technique learning toward soccer skill learning outcome, but tactical approach give more significant influence toward learning outcome of soccer skill compared with technique learning approach.